Understanding communication research methods a theoretical and practical approach - Croucher, Stephen Michael 1978-; Cronn-Mills, Daniel (Routledge, an imprint of the Taylor & Francis Group, 2022)
"Using an engaging how-to approach that draws from scholarship, real-life, and popular culture, this textbook, now in its third edition, offers students practical reasons why they should care about research methods and offers a practical guide to actually conducting research themselves. Examining quantitative, qualitative, and critical research methods, this new edition helps undergraduate students better grasp the theoretical and practical uses of method by clearly illustrating practical applications. The book features all the main research traditions within communication including online methods, and provides level-appropriate applications of the methods through theoretical and practical examples and exercises, including new sample student papers that demonstrate research methods in action. This third edition also includes additional chapters on both experimental design and methods of performance as method, as well as brand new case studies throughout. This textbook is perfect for students and scholars using critical, cultural, interpretive, qualitative, quantitative and positivist research methods, as well as students of communication studies more generally. It also offers dedicated student resources on the Routledge.com book page and instructor resources at https://routledgetextbooks.com/textbooks/instructor_downloads/. These include links, videos, outlines and activities, recommended readings, test questions, and more."--Provided by publisher.